Curve Number Analysis in the Upper Euphrates Basin to Support Regional Decision-Making - Alrammahi, Faris Sahib; Al-Madhlom, Qais Hatem Mohammed; Jassim, Sanaa Abdulrazaq (Engineering, Technology & Applied Science Research, 2025)
This study examines changes in land use and soil types in the Upper Euphrates River Basin from 2017 to 2023, and their impact on Curve Number (CN) values, a key hydrological tool for estimating surface runoff. The study area is located within the upper Euphrates River Basin, extending from Turkey and Syria to the Iraqi border at Al-Qaim. The study utilized remote sensing and geographic information system techniques, employing the Soil Conservation Service – Curve Number (SCS-CN) method and the HEC-GeoHMS model. The results revealed a significant increase in the area of natural pastures, a marked decline in Barren lands, and a relative expansion of agricultural and Built-up land. Gypsisols and Calcisols were found to be the most widespread soils, exhibiting medium to high permeability. These changes led to a gradual decrease in high CN values (79-84) and an increase in average values (64-69), reflecting improved soil permeability and reduced flood risk, while increasing the region’s resistance to drought. The study proposes adopting sustainable water policies in Iraq and enhancing regional cooperation to address the ongoing decline in the flow of the Euphrates River, which has decreased by 50% between 2000 and 2023.